The prevalence, comorbidities, influencing factors, and identifying factors of non-obese fatty liver disease - Gao, Ning; Deng, Jiang; Wang, Jinhai; Zhou, Zhihua; Yao, Cong; Zhou, Mimi; Xing, Xin; Wang, Qian; Lu, Xiaolan; Shi, Haitao (Frontiers in Medicine, 2022)
Objective To analyze the prevalence, associated comorbidities, influencing factors, and identifying factors of non-obese fatty liver disease and to provide a reference for its prevention and treatment. Materials and methods Firstly, to screen data obtained from the physical examinations of individuals conducted in the Second Affiliated Hospital of Xi’an Jiaotong University in 2021, subjects with complete data of abdominal ultrasonography, body mass index, age and sex were selected to analyze the prevalence of fatty liver disease and non-obese fatty liver disease. Secondly, to screen non-obese subjects who had data for triglycerides, fasting blood glucose, and so on, to analyze the complications, influencing factors, and identifying factors of non-obese fatty liver disease. Results The prevalence of fatty liver disease was 27.8% (18,416/66,221), including 33.9% (11,921/35,131) in males and 20.9% (6,495/31,090) in females, revealing that the prevalence was significantly higher in males than in females (P < 0.001). There were 40,673 non-obese subjects screened in total, and the prevalence of non-obese fatty liver disease was 13.0% (5,307/40,673). The prevalence of non-obese fatty liver disease was 13.3% (2,208/16,572) in males and 12.9% (3,099/24,101) in females; the difference was not statistically significant (P = 0.17). The serum triglycerides level was elevated in 54.2% of subjects with non-obese fatty liver disease, and this was the most common abnormal metabolic index accompanying the disease. Logistic regression analysis showed that gender, age, body mass index, blood pressure, alanine aminotransferase, aspartate aminotransferase, fasting blood glucose, triglycerides, total cholesterol, and serum uric acid were independent risk factors for non-obese fatty liver disease (P < 0.001). For triglycerides, the area under the receiver operating characteristic curve in predicting non-obese fatty liver disease was the greatest (0.806). Conclusion The prevalence of fatty liver disease and non-obese fatty liver disease determined by the physical examination of individuals was high, and the triglycerides is likely to be useful for the extensive screening of non-obese fatty liver disease.